REGULATORY PREREQUISITES FOR THE DEVELOPMENT OF THE MINERAL RESOURCE MANAGEMENT SYSTEM OF THE STATE SUBSOIL FUND OF UKRAINE - LYTVYNIUK, Stanislav (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2024)
Background. After the declaration of independence, the Ukrainian geological industry inherited regulatory and methodical structure and mechanisms that were formed within the framework of economic, social and other conditions typical for the former Soviet republics. Since then, fundamental changes occurred in the subsoil use legislation and the mineral and raw material base formation in Ukraine. In the context of determining the prerequisites for the development of the reliable mineral resource management system, the current regulatory framework analysis, the identification of its shortcomings and the development of an effective policy of integrated mineral resource management are quite relevant. Methods. During the analysis of the current regulatory and legal situation and its changes in the past, a wide range of studies has been used, which includes general theoretical methods of scientific and applied research. In addition to the general theoretical methods of analysis, statistics and systematization, a structural analysis of the regulatory and legal framework of the geological industry has been conducted to achieve the set goal.Results. A general regulatory and legal analysis of geological institutions’ functioning has been performed. The list of institutions and enterprises dealing with geological study, industrial development, accounting, monitoring and control related to mineral resources has been determined. The institutional relationship of stakeholders has been established during the implementation of state programs that form the main management strategy of the state subsoil fund of Ukraine. Conclusions. A comprehensive analysis of regulatory policy in the field of mineral resource management reveals circumstances that need to be considered when updating and introducing amendments to current strategies. The development of the effective mineral resource management system is possible within the framework of approved national strategic programs. The functioning and development of such management system is crucial for achieving balanced resource management in the face of rapidly growing industrial needs.
Keywords: geological industry; mineral raw materials; State Geological Survey; subsoil use